Pengaruh Manajemen Kelas Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Di Madrasah Tsanawiyah (MTs) Batusitanduk Kabupaten Luwu - Tasdin Tahrim; Nursaeni; Muhazzab Said; Alauddin; Firman Patawari; Hariati (Journal of Cross Knowledge, 2025)
This research aims to determine the implementation of classroom management at MTs Batusitanduk, to find out the learning outcomes of students' moral beliefs at MTs Batusitanduk, to determine the effect of classroom management on student learning outcomes in the moral aqidah subject at MTs Batusitanduk. This type of research is quantitative research by designex post facto. The population of all students in grades VII and VIII at MTs Batusitanduk is 164 students, with sampling using the Slovin formula. So the sample used was 62 students. Data collection techniques use questionnaires and documentation, while data analysis techniques use descriptive statistical analysis,inferential statistical analysis,Correlation analysis, simple linear regression analysis, hypothesis testing, and coefficient of determination using Microsoft Excel 2016 and SPSS version 23. The research results show that: 1) The implementation of classroom management at MTs Batusitanduk is in the categoryhigh categorywith an average percentage value of48%of the 62 students who were used as respondents; 2)Student Learning Results in Moral Creed Subjects at Madrasah Tsanawiyah (MTs)is in the high category with an average percentage value of 48%; 3) There is a significant influence betweenClass management on student learning outcomes in the subject of moral beliefs at Madrasah Tsanawiyah (MTs) Batusitandukas big as61.9%while the rest38.1%influenced by other variables not examined in this research and the significance value is 0.000 <0.05